Uso de antioxidante nos farelos de castanha de caju e de coco na alimentação de aves - Lopes, Irani Ribeiro Vieira (2007)
Feeding is one of the item that more the economic exploration of birds burdens. In the State of the Ceará this problem if accents, mainly due the necessity to import maize and soy of other states and countries (in the case of the maize) and of the sazonal oscillation in the prices of these ingredients. In the attempt to reduce the costs, if it has looked for to use “alternative” foods, as the cashew chestnut bran (FCC) and the bran of coconut (FC) in the formularization of rations for birds. In general, these brans are rich in lipídios and are inclined to develop oxidativa, main rancidez responsible for the losses of quality of foods. To prevent the lipídica peroxidação it is common to treat ingredients or rations with antirust substance during the storage. The present work had as objective to evaluate the oxidativa stability of the FCC and the FC, dealt or not with BHT (hidroxitolueno Butil) in different times of storage, and the effect of the use of these ingredients in the rations on the zootécnico performance of chickens of cut and commercial poedeiras, respectively. For each ingredient, the acquired amount was divided in five equal parts. In day zero (soon after the improvement), one of the parts was dealt with BHT, in the ratio of 500 ppm, while another one remained without the antirust substance addition until the end of 35 days of storage. In the too much portions the BHT was added to the 7, 14 and 21 days. Weekly, the peroxide and acid values had been determined (WENT) (IP). Passed the period of storage, the FCC and the FC had been used in the formularization of the rations for chickens of cut (Experiment 1 with FCC) and for commercial poedeiras (Experiment 2 with FC). In experiment 1 480 young chickens of one day had been used, Ross, distributed to perhaps in five treatments, with eight repetitions of twelve birds each. The treatments had consisted of isonutrientes rations contend: FCC without BHT addition (s/BHT); FCC with addition of BHT in day zero (BHT/0); FCC with BHT addition 7 days after the storage (BHT/7); FCC with BHT addition 14 days after the storage (BHT/14); FCC with BHT addition 21 days after the storage (BHT/21). IT WENT IT of the FCC during the period of storage did not vary, independent of the use or not of antirust substance, whereas, the IP of the FCC with or without BHT increased with the storage time. The treatments had not affected the performance (consumption of ration, profit of weight and alimentary conversion), the characteristics of carcass (chest and carcass income and, percentage of liver and abdominal fat) the text of humidity of the liver and the text of humidity and etéreo extract of the abdominal fat of the cut chickens. The parameters of quality of the meat (losses for firing, capacity of water retention, force of shear and pH) and the components of color luminosity (L*) and intensity of red (a*) of the fat had not differed between itself. However, in the group of the birds that had received FCC dealt with BHT/0 the etéreo extract text of the liver was lesser and the yellow intensity (component b*) of the abdominal fat was bigger when compared with the one of the birds of the treatment it has controlled. In experiment 2, 180 white poedeiras Hisex had been used, in as the cycle of production, distributed to perhaps in five treatments and six repetitions of six birds each. The treatments had consisted of isonutrientes rations contend: FC without BHT addition (s/BHT); FC with addition of BHT in day zero (BHT/0); FC with BHT addition 7 days after the storage (BHT/7); FC with BHT addition 14 days after the storage (BHT/14); FC with BHT addition 21 days after the storage (BHT/21). IT WENT IT and IP of the FC stored with or without BHT, had increased with the storage time. The level of oxidation observed in the FC and, consequentemente, in the rations, did not affect the productive performance (consumption of ration, percentage of position, egg mass and alimentary conversion) and the quality of eggs (weight of the egg, Haugh Units, egg yolk percentage, rind and albúmen, and color of the egg yolk). The FCC and the FC stored per 35 days without antirust substance can compose the rations of cut chickens and poedeiras, respectively, without harming the productive performance and the quality of the meat and eggs. However, fed chickens of cut with ration I contend 15% of FCC dealt with BHT/0 present minor text of etéreo extract in the liver and greater yellow intensity in the abdominal fat.